Estrategia efectiva para el impacto en la comunicación bidireccional, en los asociados a fondos de empleados en Colombia (2020)
Purpose - Seeing the communication problems within an employee fund and its mostly elder population of associates, this project purpose was focused in providing a communication strategy, capable of providing useful insights to employee funds in regards of their associates desires, needs and doubts towards the benefits, news and overall operations inside the fund. Also, a grand purpose for this project was to give employee funds associates the visible, palpable voice and empowerment they were asking for, based in community, solidarity and participation, so they can truly see and ask for the correct exploitation of the money they provide the fund. Design/methodology/approach - The methodology for this project focused on user centered design, divided in 4 main components, based on the double diamond design methodology: Contextualization, Observation, Ideation and Development. These 4 components were all worked along and co-created with the users, so every insight and discovery was provided by them comments, questions, actions and activities. In this sense, the main approach was to provide the fund and its associates a solution that resulted familiar and really listened to their needs.